Arduino based Open Source Electronic Control Unit for Electric Utility Vehicles - Francisco, Alexandre (2022)
This paper presents the design and development of a low-cost Electronic Control Unit (ECU), aimed for the application and control of Electric Utility Vehicles (EUV). The selection of components and features, as well the design and project of all the necessary hardware, was also carried out. The major features that overcome other available solutions are: multiple Controller Area Network (CAN) buses, electrical isolation of inputs, outputs, two CAN buses and serial interface, outputs with current feedback and its reduced overall cost. Validation tests were conducted in order to verify all functionalities. Moreover, an electric vehicle simulator was developed to assess the performance of the ECU in a real world working environment. The fully functional prototype of the ECU proved to be robust and experimental results fulfill the proposed objectives.